KELEMBAGAAN MASYARAKAT DALAM PENGELOLAAN HUTAN ADAT (Studi Kasus di Kasepuhan Pasir Eurih, Desa Sindanglaya, Kecamatan Sobang, Kabupaten Lebak, Provinsi Banten) - Rushestiana Pratiwi; Tb Unu Nitibaskara; Messalina L Salampessy (Forestry Study Program University Of Mataram, 2019)
Indigenous peoples have a down-to-down knowledge of how to preserve and utilize existing forest resources. The role of indigenous peoples in the management of indigenous forest resources is essential in maintaining the viability of forest functions. For this reason this study aims to describe and explain the potential of community institutions in the management of customary forests in Kasepuhan Pasir Eurih Sindanglaya Village. The research method is case study where data is collected through interview and observation. Data analysis is done by using Situation framework approach - Structure - behavior - performance. The results show that the use of customary forest is considered open access where everybody is free to exploit the natural resources in it. Behavior shows the presence of stakeholders affecting customary forest management activities. Community performance in customary forest management shows that customary forests strongly support the welfare of indigenous peoples.